Characteristics of Farmers in Etawah Crossbreed (PE) Goat Breeding Center of Banyumas Regency, Indonesia - Sari Eko Tuswati; Akhmad Sodiq; Novie Andri Setianto; Doso Sarwanto; Agustinah Setyaningrum; Setya Agus Santosa (Journal of Sustainable Livestock, 2026)
This survey research was conducted in the Etawah Crossbreed (Peranakan Etawah/PE) goat breeding center of Gumelar District, Banyumas Regency, involving 75 active farmers. Primary data were collected via observation and interviews, while secondary data came from government institutions and literature. Results showed that etawah crossbreed goat farmers are predominantly mature, averaging 57.17 years old (41.33% aged 51-60 years). Their formal education is mostly limited to elementary school (65.33%). Regarding livelihood, 65.33% are primarily crop farmers, making goat rearing a synergistic supplementary business. The average family size is 4 members (64.00% have 4-5 members), providing essential unpaid labor for daily operations. Despite limited formal education, these farmers possess extensive practical experience averaging 20.20 years. In conclusion, the profile of etawah crossbreed goat farmers in Gumelar District, Banyumas, reflects a traditional, family-supported enterprise where extensive experience significantly compensates for the lack of formal education, serving as a strategic secondary income alongside crop farming.